1987
DOI: 10.1113/jphysiol.1987.sp016457
|View full text |Cite
|
Sign up to set email alerts
|

Fluid absorption by rat lung in situ: pathways for sodium entry in the luminal membrane of alveolar epithelium.

Abstract: SUMMARY1. The purpose of the investigation was to characterize the luminal membrane and the paracellular pathway of rat lung alveolar epithelium. Experiments were performed on lungs in situ instilled with isotonic, buffered Ringer solution and perfused with blood from a donor rat using cross-circulation technique.2. The rate of active Na+ transport was 4-4 pmol/(cm2 s). The fluid absorption was 156 nl/s, and was unaffected by the presence of protein in the instillate (166 nl/s). In the absence of Na+, fluid ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 43 publications
(64 reference statements)
8
83
0
2
Order By: Relevance
“…The initial rates of fluorescence increase are shown by the dashed lines in each curve. Note the slower initial rates in lungs at FD31 and just after birth (1 and 4 h) compared to lungs from older rabbits (12,36, and 60 h). By 120 h after birth, the initial rate of fluorescence increase was decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial rates of fluorescence increase are shown by the dashed lines in each curve. Note the slower initial rates in lungs at FD31 and just after birth (1 and 4 h) compared to lungs from older rabbits (12,36, and 60 h). By 120 h after birth, the initial rate of fluorescence increase was decreased.…”
Section: Resultsmentioning
confidence: 99%
“…By 12 h after birth, 80% of perinatal lung liquid is cleared (8)(9)(10). The ability to osmotically reabsorb fluid from the airspaces is retained throughout adult life (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…All of this prepared the lungs for labor induction, having an additive stimulatory effect on lung fluid absorption after IL-1␤ stimulation and preterm delivery. It has also been demonstrated (3,5,6,19,31) that lung fluid is reabsorbed secondary to Na ϩ absorption and that this Na ϩ transport can be stimulated by agonist binding to ␤-adrenoceptors. Consequently, more ␤-adrenoceptors and higher ␤-adrenoceptor stimulation may lead to increased Na ϩ and fluid transport.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1␣ also improved postnatal lung function with increased surfactant pool size without eliciting systemic inflammatory responses in lambs (14, 47). We recently reported that IL-1␤ pretreatment of timed-pregnant guinea pigs induced fluid absorption in fetal lungs, sodium transporter protein, and ␤-adrenoceptor expression via hypothalamus-pituitary-adrenal gland axis stimulation (48).Lung fluid absorption occurs secondarily to transepithelial Na ϩ absorption (3,5,8,17,22,31,35,37,45,48,49) and is driven by basolateral Na-K-ATPases (16, 23) and apical epithelial sodium channels (19,22,30,31). Fluid absorption occurs in near-term lungs (6,17,35,37,45) and is induced/ stimulated by cortisol and triiodothyronine (2, 20, 48) and labor-released epinephrine (17,35,45).…”
mentioning
confidence: 99%
“…During acute respiratory distress syndrome or at high altitude, alveoli flood with edema, thus impairing gas exchange (33). Active sodium transport is the primary mechanism responsible for removal of fluid from the distal air spaces (3). Overall, the process of transepithelial sodium transport can be considered a two-step process.…”
Section: Effect Of Hypoxia On Proteins Involved In Glucose Metabolismmentioning
confidence: 99%